2019
DOI: 10.3390/cancers11010116
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan-Based Third-Line Therapy Has a Higher Eradication Rate against Sitafloxacin-Resistant Helicobacter pylori

Abstract: Eradication of Helicobacter pylori (H. pylori) is an effective strategy for preventing various gastrointestinal diseases such as gastric cancer and mucosa-associated lymphoid tissue (MALT) lymphoma. However, the eradication success rate is decreasing because of a recent increase in drug-resistant strains of H. pylori. Here, we evaluated the success rate of eradication therapy with vonoprazan (VPZ), a new potassium-competitive acid blocker, against drug-resistant H. pylori. In total, 793 patients who received H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…The promising point in their study was the well-tolerated rate of vonoprazan-based therapy in patients. Recently, Saito et al (2019) have shown that the dual therapy using vonoprazan and amoxicillin can brings a higher eradication rate than standard H. pylori treatment. With this regard, in a Randomized Control Trial, Ozaki et al (2018) concluded that vonoprazan is the future of successful therapy of H. pylori in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…The promising point in their study was the well-tolerated rate of vonoprazan-based therapy in patients. Recently, Saito et al (2019) have shown that the dual therapy using vonoprazan and amoxicillin can brings a higher eradication rate than standard H. pylori treatment. With this regard, in a Randomized Control Trial, Ozaki et al (2018) concluded that vonoprazan is the future of successful therapy of H. pylori in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effectiveness of vonoprazan (a first-inclass potassium-competitive acid blocker), AMX and STFX-containing regimens (VAS) is reported to be superior to a compared EAS regimen. However, the previous reports did not reveal the relationship between the efficacy and gyrA mutation [14,15]. Considering our results, confirmation of the superiority of VAS to EAS against gyrA mutation-positive strains is essential.…”
Section: Discussion/conclusionmentioning
confidence: 46%
“…A study revealed that the third-line vonoprazan-based regimen has a higher H. pylori eradication rate than the PPI-based regimen (75.8% vs. 53.3%) [ 78 ]. Another study also showed the vonoprazan-based regimen has a higher eradication rate against sitafloxacin-resistant H. pylori than esomeprazole-based regimens (91.7% vs. 71.2%) [ 79 ]. Studies on third-line H. pylori eradication therapies are limited because third-line therapies are not covered under the universal Japanese health insurance [ 80 ].…”
Section: Clinical Benefits Of Vonoprazanmentioning
confidence: 99%